A consistent measure of the merger histories of massive galaxies using close-pair statistics I: Major mergers at z < 3:5 - Mundy, Carl J.; Conselice, Christopher J.; Duncan, Kenneth J.; Almaini, Omar; Häußler, Boris; Hartley, William G. (Oxford University Press, 2017)
We use a large sample of ∼350,000 galaxies constructed by combining the UKIDSS UDS, VIDEO/CFHT-LS, UltraVISTA/COSMOS and GAMA survey regions to probe the major merging histories of massive galaxies (>1010 M⊙) at 0.005<z<3.5. We use a method adapted from that presented in Lopez-Sanjuan et al. (2014) using the full photometric redshift probability distributions, to measure pair fractions of flux-limited, stellar mass selected galaxy samples using close-pair statistics. The pair fraction is found to weakly evolve as ∝(1+z)0.8 with no dependence on stellar mass. We subsequently derive major merger rates for galaxies at >1010 M⊙ and at a constant number density of n>10−4 Mpc−3, and find rates a factor of 2-3 smaller than previous works, although this depends strongly on the assumed merger timescale and likelihood of a close-pair merging. Galaxies undergo approximately 0.5 major mergers at z<3.5, accruing an additional 1-4 ×1010 M⊙ in the process. Major merger accretion rate densities of ∼2×10−4 M⊙ yr−1 Mpc−3 are found for number density selected samples, indicating that direct progenitors of local massive (>1011M⊙) galaxies have experienced a steady supply of stellar mass via major mergers throughout their evolution. While pair fractions are found to agree with those predicted by the Henriques et al. (2014) semi-analytic model, the Illustris hydrodynamical simulation fails to quantitatively reproduce derived merger rates. Furthermore, we find major mergers become a comparable source of stellar mass growth compared to star-formation at z<1, but is 10-100 times smaller than the SFR density at higher redshifts.